Solubility Enhancement of Flavonols in the Inclusion Complex with Thioether-bridged Dimeric β-Cyclodextrins - Cho, Eunae; Jeong, Daham; Paik, Hyun-Dong; Jung, Seunho (Bulletin of the Korean Chemical Society, 2014)
Dimeric β-cyclodextrin linked by a thioether bridge was synthesized from a reaction of mono-6-iodo-6-deoxy- β-cyclodextrin with sodium sulfide, and the structure was analyzed using nuclear magnetic resonance spectroscopy and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The effects of thioether-bridged dimeric β-CD on the aqueous solubility of flavonols (myricetin, quercetin, and kaempferol) were investigated by ultraviolet-visible spectroscopy. The aqueous solubility of myricetin, quercetin, and kaempferol were enhanced 33.6-, 12.4-, and 10.5-fold following the addition of 9 mM of thioether-bridged dimeric β-CD. In comparison, the aqueous solubility of myricetin, quercetin, and kaempferol were enhanced 5.4-, 3.3-, and 2.7-fold using the same concentration of monomeric β-cyclodextrin. Furthermore, the formation of flavonol/thioether-bridged dimeric β-CD inclusion complexes was confirmed with nuclear magnetic resonance, Fourier-transform infrared spectroscopy, differential scanning calorimetry, and scanning electron microscopy. The results showed that the nature of the complexes significantly differed from that of free flavonols. Herein, we suggest that the thioether-bridged dimeric β-CD can act as an effective complexing agent for flavonols. KCI Citation Count: 6